2014
DOI: 10.3149/jms.2202.105
|View full text |Cite
|
Sign up to set email alerts
|

Men at the Crossroads: A Profile Analysis of Hypermasculinity in Emerging Adulthood

Abstract: The purpose of this study is twofold: to evaluate the factor structure of the Auburn Differential Masculinity Index and to investigate the varied adoption of hypermasculine attitudes within a sample of 328 collegiate males (M = 19.50, SD = 1.53). Factor analytic procedures were used to determine a factor structure that provided the best fit for the data. Four dimensions emerged: dominance & aggression, sexual identity, anti-femininity, and devaluation of emotion. Cluster analytic methods were used to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…This insignificant finding for the role of hypermasculinity contrasts with traditional literature that typically finds strong direct associations between hypermasculinity and sexual violence [35,36]. More recent research, however, has also noted some inconsistencies of the effect of hypermasculinity on sexual aggression toward women and suggested that perhaps hypermasculinity is not a unidimensional concept, but rather a multidimensional concept with varying dimensional impacts [37,38]. It is possible that some dimension of hypermasculinity can manifest as a protective instinct where men intend to honor and protect their partner.…”
Section: Discussionmentioning
confidence: 73%
“…This insignificant finding for the role of hypermasculinity contrasts with traditional literature that typically finds strong direct associations between hypermasculinity and sexual violence [35,36]. More recent research, however, has also noted some inconsistencies of the effect of hypermasculinity on sexual aggression toward women and suggested that perhaps hypermasculinity is not a unidimensional concept, but rather a multidimensional concept with varying dimensional impacts [37,38]. It is possible that some dimension of hypermasculinity can manifest as a protective instinct where men intend to honor and protect their partner.…”
Section: Discussionmentioning
confidence: 73%
“…These results may be due to the emerging adult sons in the study reporting lower anxiety symptoms than emerging adult daughters; low anxiety levels might produce negligible effects. Similarly, it may be less acceptable for males to be highly religious or highly anxious within a hypermasculinized context such as college (Corprew et al, 2014). Females also may benefit more from religion while in college due to the degree of social support that religiosity can contribute to female college students’ lives (Shiah et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, a pair of scores on the CPI cannot capture the complete essence of being a man or woman in American society. Additional nuanced examination of aspects of lived experience, including subtypes of men and women, is needed (e.g., Corprew, Matthews, & Mitchell, 2014).…”
Section: Discussionmentioning
confidence: 99%